2001
DOI: 10.1101/gad.891901
|View full text |Cite
|
Sign up to set email alerts
|

FIERY1 encoding an inositol polyphosphate 1-phosphatase is a negative regulator of abscisic acid and stress signaling in Arabidopsis

Abstract: The plant hormone abscisic acid (ABA) plays a wide range of important roles in plant growth and development, including embryogenesis, seed dormancy, root and shoot growth, transpiration, and stress tolerance. ABA and various abiotic stresses also activate the expression of numerous plant genes through undefined signaling pathways. To gain insight into ABA and stress signal transduction, we conducted a genetic screen based on ABA-and stress-inducible gene transcription. Here we report the identification of an A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
384
3
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 348 publications
(417 citation statements)
references
References 44 publications
24
384
3
6
Order By: Relevance
“…era1, abh1, and gcr1) with enhanced response to ABA have been shown to cause reduced water consumption (Pei et al, 1998;Hugouvieux et al, 2001;Pandey and Assmann, 2004), many examples of mutants that do not match this assertion are known. For instance, the fry1 and sad1 mutants, which show ABAhypersensitive inhibition of seed germination and superinduction of ABA-responsive genes, have compromised tolerance to drought stress (Xiong et al, 2001a(Xiong et al, , 2001b. Likewise, the calcineurin B-like 9, the calcineurin B-like-interacting protein kinase, and the APETALA2-like ABA repressor 1 mutants, which display ABA hypersensitivity and enhanced expression of ABA signaling genes, do not correlate with stresstolerance phenotypes Pandey et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…era1, abh1, and gcr1) with enhanced response to ABA have been shown to cause reduced water consumption (Pei et al, 1998;Hugouvieux et al, 2001;Pandey and Assmann, 2004), many examples of mutants that do not match this assertion are known. For instance, the fry1 and sad1 mutants, which show ABAhypersensitive inhibition of seed germination and superinduction of ABA-responsive genes, have compromised tolerance to drought stress (Xiong et al, 2001a(Xiong et al, , 2001b. Likewise, the calcineurin B-like 9, the calcineurin B-like-interacting protein kinase, and the APETALA2-like ABA repressor 1 mutants, which display ABA hypersensitivity and enhanced expression of ABA signaling genes, do not correlate with stresstolerance phenotypes Pandey et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recessive mutations leading to ABA hypersensitivity were found in the era1 (Cutler et al, 1996), abh1 ), fry1 (Xiong et al, 2001b), hypersensitive to ABA1 (hab1; Leonhardt et al, 2004;Saez et al, 2004), sad1 (Xiong et al, 2001a), and gcr1 (Pandey and Assmann, 2004) mutants. The intragenic revertants of abi1-1 and abi1-1R1 to R7 also carry recessive mutations that lead to enhanced responsiveness to ABA (Gosti et al, 1999).…”
mentioning
confidence: 99%
“…In addition, the identification of a phenotypically related human skeletal disease resulting from mutations in gPAPP confirms that Golgi-resident 3′-nucleotidase activity is essential for sulfation-dependent processes such as cartilage formation and long bone growth (14). Conversely, functional studies in bacteria and yeast have implicated the more ancient cytosolic 3′-nucleotidase Bpnt1 in numerous sulfation-independent processes, including salt tolerance and methionine biosynthesis (15)(16)(17)(18)(19)(20)(21)(22)(23). Thus, although it is clear that gPAPP is essential for proper Golgimediated sulfation, the role of Bpnt1 in mammals and its potential connection to cytosolic sulfation remains unclear.…”
mentioning
confidence: 99%
“…The fry1 mutation leads to sustained accumulation of IP 3 and hypersensitivity to ABA, cold and salt stress. Thus, IP 3 plays a crucial role in cytosolic Ca 2+ oscillations during ABA, salt and cold stress signaling (26).…”
Section: Second Messengersmentioning
confidence: 99%
“…Excess Na + -induced membrane depolarization may activate mechanosensitive Ca 2+ channels to generate Ca 2+ signature under salt stress (4,17). Pharmacological studies and genetic analysis have shown the involvement of inositol 1,4,5-tris phosphate (IP 3 )-gated Ca 2+ channels in the regulation of Ca 2+ signature during salt stress (24)(25)(26). The FRY1 locus of Arabidopsis encodes an inositol polyphosphate 1-phosphatase, which catabolizes IP 3 .…”
Section: Second Messengersmentioning
confidence: 99%